Emphysematous pyelonephritis – A case series from a single centre in Southern India - Alaparthi, Phanisri; Rao, Shobhana Nayak; M, Pradeep Shenoy (Journal of Clinical Nephrology, 2018)
TEmphysematous pyelonephritis (EPN) is a rare but potentially life-threatening necrotizing renal parenchymal infection characterised by the production of intra-parenchymal gas. The approach and the management of emphysematous has changed dramatically over the last two decades with the advent of computed tomography (CT)-based diagnosis and advances in antibiotic therapy as well as multidisciplinary intensive care of sepsis leading to an overall decline in mortality rates to 20-25%. The previously standard treatment for EPN which included nephrectomy of the affected kidney has been replaced by minimally invasive and nephron sparing surgery with better patient outcomes. We present our case series of 12 patients with EPN over a short period of two years treated at our tertiary care centre in South Western India.